Implementasi Prinsip Good Governance Di Lingkungan Sekretariat Daerah Kota Banjar: Studi: Sekretariat Daerah Kota Banjar - Rifal Amalindi; Hamdan Ihwani; Arie Budiawan (Journal of Research and Development on Public Policy, 2023)
This research is motivated by the implementation of the principles of good governance within the Regional Secretariat of the City of Banjar which is currently running but not optimally. This is proven by the fact that there are still several inhibiting factors in the implementation of the principles of good governance including: there are still developments being carried out, discrepancies in the placement of State Civil Apparatus employees in their fields, not yet being fully transparent to the public, giving rise to the notion that the government is anti-criticism, as well as employee adjustments which tends to be slow towards dynamic legal rules. The research method used was qualitative research, data collection techniques through observation and interviews with informants at the Regional Secretariat of the City of Banjar totaling 1 Regional Assistant, 5 Section Heads, and 3 Staff. Based on the research conducted, it can be concluded that: The implementation of the principles of good governance include Accountability, Transparency, Openness, and the Rule of Law in practice will be realized